Interrelationship between oil content and fatty acid composition in Indian soybean - RANI, ANITA; KUMAR, VINEET; VERMA, SANDEEP K; SHAKYA, ARVIND K; HUSSAIN, S M; CHAUHAN, G S (The Indian Journal of Agricultural Sciences, 2011)
Soybean genotypes are being sought after that possess not only high oil content but also high oleic acid and low linolenic acid, the fatty acids that influence the storage stability of oil. In the present investigation, oil content and fatty acid composition of mature seeds of soybean cultivars/strains were determined and their interrelationship was studied. The oil content ranged from 13.0 to 21.85% while a range of 18.78-36.80% for oleic, 40.97-59.98% for linoleic, 5.5- 10.55% for linolenic acid was observed. Significant negative correlation (P